2020
DOI: 10.3390/rs12121977
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of SMAP Operational Soil Moisture Product from a Global Perspective

Abstract: Space-borne soil moisture (SM) satellite products such as those available from Soil Moisture Active Passive (SMAP) offer unique opportunities for global and frequent monitoring of SM and also to understand its spatiotemporal variability. The present study investigates the performance of the SMAP L4 SM product at selected experimental sites across four continents, namely North America, Europe, Asia and Australia. This product provides global scale SM estimates at 9 km × 9 km spatial resolution at daily interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 60 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…A possible cause for the positive bias reported by this study's results could be uncertainties resulting from ancillary data parameterizations [7,59]. In the SCA-V, brightness temperature (TB) is converted to emissivity by correcting for the effective soil temperature effect, vegetation, and surface roughness.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…A possible cause for the positive bias reported by this study's results could be uncertainties resulting from ancillary data parameterizations [7,59]. In the SCA-V, brightness temperature (TB) is converted to emissivity by correcting for the effective soil temperature effect, vegetation, and surface roughness.…”
Section: Discussionmentioning
confidence: 91%
“…A mismatch between the satellite sensor and the measuring depth of the in situ instrument and the discrepancy between the in situ SSM measuring depth and the satellite depth of microwave penetration could explain, in part, the bias displayed in some of the grids. The sensing depth of the L-band is shallow compared with the in situ instruments [7,54]. The ground-based measurements used to validate the products are placed at a depth of approximately 5 cm and usually observe SSM at a depth of 3 to 7 cm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to its continuity, SMAP has attracted more attention and is more widely used. Experiments based on several sites have shown that SMAP performed well in North America [14]. SMAP can also be used to compare the performance of different observation networks, but the temporal variation of soil moisture cannot be detected [15].…”
Section: Introductionmentioning
confidence: 99%